Rancang Bangun Visualisasi Informasi Akademik Menggunakan Sistem Dashboard di SMA Negeri 12 Surabaya - Perdana, Amryzal; Hariadi, Bambang; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
At this time, High school 12 Surabaya is one of the favorite High School in West Surabaya area with a level of accreditation with the value of accreditation is 87. With the value of accreditation 87, is still not considered to be maximum by the principal of High school 12 Surabaya because the value of accreditation is still not safe for value accreditation in High school, High school school 12 Surabaya determined to improve the value of academic performance to fit the 8 components of accreditation.To support the plan, needed a system that can give information about the condition of academic performance that occurs this time appropriate with the supporting component in the accreditation assessment. One alternative to solve this problem is build a system that can give the right information in the academic performance to fit 8 components of accreditation. The information displayed in the form of the dashboard, with a variety of formats such as graphs, gauges, charts and indicators which can allow a user to analyze important information